The intersection between migration, HIV, and contraceptive use in Uganda: a cross-sectional population-based study - Prossy Namusisi; Ping Teresa Yeh; Robert Ssekubugu; Larry William Chang; Tom Lutalo; Linnea Zimmerman; Mary Kathryn Grabowski (BMC, 2024)
Abstract Background Low use of modern methods of contraception has been linked to HIV seropositivity and to migration, but few studies have evaluated the intersection of both risk factors with contraceptive use. Methods We analyzed cross-sectional data from sexually active female participants aged 15 to 49 years in the Rakai Community Cohort Study (RCCS) between 2011 and 2013. The RCCS is an open population-based census and individual survey in south-central Uganda. Recent in-migrants (arrival within approximately 1.5 years) into RCCS communities were identified at time of household census. The primary outcome was unsatisfied demand for a modern contraceptive method (injectable, oral pill, implant, or condom), which was defined as non-use of a modern contraceptive method among female participants who did not want to become pregnant in the next 12 months. Poisson regression models with robust variance estimators were used to identify associations and interactions between recent migration and HIV serostatus on unsatisfied contraceptive demand. Results There were 3,417 sexually active participants with no intention of becoming pregnant in the next year. The mean age was 30 (± 8) years, and 17.3% (n = 591) were living with HIV. Overall, 43.9% (n = 1,500) were not using any modern contraceptive method. Recent in-migrants were somewhat more likely to have unsatisfied contraceptive demand as compared to long-term residents (adjusted prevalence risk ratio [adjPRR] = 1.14; 95% confidence interval [95%CI]: 1.02-1.27), whereas participants living with HIV were less likely to have unsatisfied contraceptive demand relative to HIV-seronegative participants (adjPRR = 0.80; 95%CI = 0.70-0.90). When stratifying on migration and HIV serostatus, we observed the highest levels of unsatisfied contraceptive demand among in-migrants living with HIV (48.7%); however, in regression analyses, interaction terms between migration and HIV serostatus were not statistically significant. Conclusions Unsatisfied contraceptive demand was high in this rural Ugandan setting. Being an in-migrant, particularly among those living with HIV, was associated with higher unsatisfied contraceptive demand.